The Establishment Period Of Turkish Grand National Assembly And The İnauguration Day Of The Assembly (23 April 1920) - Erdem, Ufuk (Fırat University, 2021)
The Chamber of Deputies of the Ottoman Empire was deactivated after the official invasion of Istanbul by the allied powers on March 16, 1920. The Chamber decided on suspending their meetings especially upon the forcible arrests of some deputies by the occupation forces in the Parliament Building. Mustafa Kemal Pasha set over upon the deactivation of the assembly by the allied powers with the aim of not leading the people’s will to be passed over and proclaimed that a national assembly would be established in Ankara. In line with this objective, he gave the military and civil senior officers the instructions related with how the elections for the new assembly would be held and how the ceremonies to be performed before the inauguration would be conducted. The 20th Corps residing in Ankara prepared a detailed and sketched programme for the deployment of the ceremonial units on the inauguration day. The present research discusses the details of the instructions and programme concerning the inauguration of the Grand National Assembly.

Osmanlı Mebusan Meclisi, 16 Mart 1920’de İstanbul’un İtilaf Devletleri tarafından resmen işgaliyle çalışamaz hale gelmiştir. Özellikle bazı milletvekillerinin meclis binasında işgal kuvvetleri tarafından zor kullanılarak tutuklanması üzerine Meclis, toplantılarına ara verme kararı almıştır. İtilaf Devletleri’nin Meclisi işlevsiz hale getirmesi üzerine millet iradesinin yok sayılmaması için hemen harekete geçen Mustafa Kemal Paşa, Ankara’da milli bir meclisin açılacağını duyurmuştur. Bu amaçla, yeni açılacak meclis için seçimlerin nasıl yapılacağı ve açılış öncesinde icra edilecek törenlerin nasıl olacağına dair talimatlar, Mustafa Kemal Paşa tarafından Anadolu’daki askerî ve mülkî erkâna gönderilmiştir. Ankara’da bulunan 20. Kolordu tarafından da açılış günü askeri tören birliklerinin nasıl konuşlanacağına dair detaylı bir krokili program hazırlanmıştır. Bu çalışmada Büyük Millet Meclisinin açılışına dair talimat ve program ayrıntıları değerlendirilmiştir
TÜRKİYE BÜYÜK MİLLET MECLİSİNİN AÇILMA SÜRECİ VE MECLİSİN AÇILIŞ GÜNÜ (23 NİSAN 1920)